Preparation and Characterization of Silver Nanoparticles Biosynthesis by Pseudomonas stutzeri Environmental Bacteria Isolated from Oil Fields and Their Antimicrobial Activity - Bachii, Sheyma Awad; Abd-Al Sahib, Wijdan Hussein; Razaq Salah, Afrodet Abd–AL (Scientific Journal of Medical Research, 2021)
Objectives: This study investigate The bacteria of Pseudomonas stutzerii was used for biosynthesized of AgNPs role of as antibacterial against burns and wounds infection pathogens. Methods: the characters of AgNPs were tested by visible ultraviolet (UV) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) analyzes. the antibacterial potential was achieved using agar well diffusion method against 90 samples were collected from burns and wounds patients the pathogenic isolates were diagnosed using a VITEK. The biological activity of AgNPs was tested against pathogenic bacteria by two methods including agar well diffusion method at concentrations (1000, 500, 250, 100 andmicro;g/ml) and dilution method at concentrations (1000, 750, 500, 250, 100 andmicro;g / ml). Results: The results of The results of genetic identification showed that the bacteria of Pseudomonas stutzerii was under the strain Pseudomonas stutzerii 0106 ,The fabricated AgNPs were found that SPR peak for AgNPs was at a wavelength of (417)nm and the FTIR many biomolecules that are responsible for the conversion of silver ion into AgNPs the shape of AgNPs were spherical with a size in the range of (22-47) nm. Identification of pathogenic bacteria revealed isolate of 15 species include Pseudomonas aeruginosa 6(12%) ,followed by Proteus mirabilis and E.coli 5(10%),Enterobacter cloacae, Burkholderia cepacia and Staphylococcus areus 4(8%), Staphylococcus Xylosus, Pseudomonas fluerescents and Pseudomonas luteola 3(6%), Staphylococcus lugdnnensis, Enterococcus colummpae, Acinetobkter buamannii and 2(4%) lastly Granulicatella elegans and Morganella morganii 1(2%). Conclusion: Silver nanoparticles Ag-NPs generated by Pseudomonas stutzreii extract were monodispersed and spherical in morphology with size a range from 15 to 30 nm. The biosynthesizedi Ag-NPs were not aggregated, indicating that the Ag-NPs have been stabilized by a cappingi agent from the bacterial extract . Ag-NPs displayed potent bactericidal activities against both Gram-positive and negative bacteria with effect on Cram-negative bacteria more than Cram-positive bacteria.